Macroalgae Diversity from San-Pedro Port Area - Adon, Marie Paulette (European Journal of Applied Sciences, 2022)
The work, one of the objectives which was to constitute a complementary reference base for the assessment biodiversity and esential habitats, was carried out within the framework the complementary studies biodiversity and sediments; Autonomous Port from San-Pédro. The methodology applied consisted in sampling macroalgae from June 10 to 14, 2021 in 5 sites located from San-Pedro Port Container Terminal, which are the turning site, the site of the channel from San-Pedro Autonomous Port, the site close to the breakwater and the area to be filled in, the marine site and the site close to the mouth and the area intended to house the marine base. The results obtained highlighted the absence of macroalgae in all the sampled sites with the exception of the site near the mouth and the area intended to accommodate the marine base in which the harvest of the red macroalgae Gelidium latifolium (Greville ) Bornet & Thuret, 1876 was realized. This macroalgae of socio-economic importance, little exploited, but used for the agar extraction is under unspecified protection by order no. 1118-83 of 93/12/1, a protective measure which could constitute a beneficial asset for the ecosystems conservation in a dynamic sustainable development and would also promote the algae cultivation with a view to their industrial exploitation.